2016
DOI: 10.1016/j.ijcard.2016.07.202
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan beyond inotropy and acute heart failure: Evidence of pleiotropic effects on the heart and other organs: An expert panel position paper

Abstract: Levosimendan is a positive inotrope with vasodilating properties (inodilator) indicated for decompensated heart failure (HF) patients with low cardiac output. Accumulated evidence supports several pleiotropic effects of levosimendan beyond inotropy, the heart and decompensated HF. Those effects are not readily explained by cardiac function enhancement and seem to be related to additional properties of the drug such as anti-inflammatory, anti-oxidative and anti-apoptotic ones. Mechanistic and proof-of-concept s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 132 publications
(156 reference statements)
0
83
0
6
Order By: Relevance
“…Since it does not act through adrenergic receptors, β blockade does not influence the hemodynamic effects of levosimendan (10). Although it is primarily used for treatment of patients with heart failure, there is growing evidence of its benefit in patients undergoing cardiac surgery (16,32). In a recently published article, it is recommended that levosimendan be used in the preoperative setting in cardiac surgery (16).…”
Section: Calcium Sensitizersmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it does not act through adrenergic receptors, β blockade does not influence the hemodynamic effects of levosimendan (10). Although it is primarily used for treatment of patients with heart failure, there is growing evidence of its benefit in patients undergoing cardiac surgery (16,32). In a recently published article, it is recommended that levosimendan be used in the preoperative setting in cardiac surgery (16).…”
Section: Calcium Sensitizersmentioning
confidence: 99%
“…In addition to its use in the treatment of heart failure and cardiac surgery, there is growing evidence of beneficial effect when levosimendan is used in other settings. Although there is strong evidence of its renoprotective effect, there are still some conflicting results (31,32). Furthermore, there is evidence that levosimendan reduces mortality in patients with severe sepsis and septic shock (33).…”
Section: Calcium Sensitizersmentioning
confidence: 99%
“…Levosimendan is a positive inotropic agent (by increasing the sensitivity of troponin C to calcium) with vasodilating properties (by lowering of intracellular free Ca++, opening of different potassium channels and the inhibition of phosphodiesterase type III), also termed inodilator [3,4]. There are several animals studies in different acute pulmonary hypertension (PH) models secondary to thromboxane A2 infusion [5], endotoxemia [6], acute pulmonary embolism (PE) [7,8], and hypoxia [9] and some clinical studies that demonstrated the vasodilator effect of levosimendan on the pulmonary circulation, restoring right ventricular-arterial coupling as it increased right ventricular contractility concomitantly [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Levosimendan exerts both inotropic and vasodilatatory effects via increasing cardiac contractility mediated by calcium sensitization of troponin C and producing vasodilation through opening adenosine triphosphate (ATP)-sensitive potassium channels in vascular smooth muscle cells. Aside from its clinical indication in treating acute decompensated HF, benefits of levosimendan have been demonstrated in other clinical conditions including cardiogenic or septic shock, cardiac surgery and advanced chronic HF [8][9][10]. First evidence for the use of levosimendan comes from 4 case reports who developed TS-related cardiogenic shock [11][12][13] or sepsisassociated TS [14].…”
mentioning
confidence: 99%